The Influence of Corporate Social Responsibility (CSR) and Firm Size on Earnings Management: Study from Listed Infrastructure Companies in Indonesia Stock Exchange (IDX) - Rahmasari, Naila Syifa; Budi, Kurniawan (Emerging Markets : Business and Management Studies Journal, 2024)
This study investigates the impact of Corporate Social Responsibility and firm size on earnings management practices among publicly listed infrastructure companies on the Indonesia Stock Exchange between 2018 and 2022. Using a Pooled Least Square regression model in STATA 14, the research analyzes data from the selected companies. The findings reveal a positive correlation between CSR, firm size, and earnings management. This suggests that companies may utilize CSR initiatives as a strategic tool to mask profit overstatements, thereby maintaining a favorable public image and attracting investors. Additionally, larger companies exhibit a higher propensity for earnings management compared to smaller firms, potentially due to the pressure to maintain a positive reputation and manage the costs associated with large-scale operations.